(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
The article provides and investigates the demand for religious tours at the regional level. The tourist flow of pilgrimage tourism in Uzbekistan is directed to the largest cities of the country and centers of spiritual culture: Tashkent, Bukhara, Samarkand, Khiva. The relevance of the research topic is due to the growing interest in religious tourism and its form of pilgrimage. Given the centuries-old Islamic heritage of Uzbekistan, the growth of religious tourism has great outlook for the country. By 2026, the number of pilgrim tourists in the world will reach 230 million. The objective of this article is to identify factors affecting the demand for religious tours in our country and to identify problems and outlooks for the growth of pilgrimage tourism in the region.